2022
DOI: 10.1111/eci.13859
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of vascular dysfunction in acute and convalescent COVID‐19: A systematic review

Abstract: Background Accumulating evidence suggests that endothelial dysfunction is implicated in the pathogenesis and severity of coronavirus disease 2019 (COVID‐19). In this context, vascular impairment in COVID‐19 might be associated with clinical manifestations and could refine risk stratification in these patients. Methods This systematic review aims to synthesize current evidence on the frequency and the prognostic value of vascular dysfunction during acute and post‐recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
(232 reference statements)
0
10
0
1
Order By: Relevance
“…We</ins> <del cite="mailto:User" datetime="2022-12-18T21 : 04">and</del> were unable to include some potentially interesting novel biomarkers, that are currently used only for research purposes. <ins cite="mailto:User" datetime="2022-12-18T21 : 04"></ins><ins cite="mailto:User" datetime="2022-12-18T21 : 05">This to be said several studies have identified endothelial dysfunction and markers of extrinsic coagulation pathway</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">to have an important role in</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 07">the pathophysiology of</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">hypercoagulation</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 10">as well as a potential prognostic impact</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">in Covid-19</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 07"></ins> [38][39][40]<ins cite="mailto:User" datetime="2022-12-18T21 : 06">.</ins> However, since our goal was to investigate the correlation of common biomarkers with VTE in clinical practice, we are convinced that it was a drawback of minor entity.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…We</ins> <del cite="mailto:User" datetime="2022-12-18T21 : 04">and</del> were unable to include some potentially interesting novel biomarkers, that are currently used only for research purposes. <ins cite="mailto:User" datetime="2022-12-18T21 : 04"></ins><ins cite="mailto:User" datetime="2022-12-18T21 : 05">This to be said several studies have identified endothelial dysfunction and markers of extrinsic coagulation pathway</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">to have an important role in</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 07">the pathophysiology of</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">hypercoagulation</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 10">as well as a potential prognostic impact</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 06">in Covid-19</ins> <ins cite="mailto:User" datetime="2022-12-18T21 : 07"></ins> [38][39][40]<ins cite="mailto:User" datetime="2022-12-18T21 : 06">.</ins> However, since our goal was to investigate the correlation of common biomarkers with VTE in clinical practice, we are convinced that it was a drawback of minor entity.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 99%
“…Endothelial impairment at the post-acute COVID-19 phase may contribute to increased arterial stiffness. The role of systemic inflammation may also affect arterial function parameters [ 42 , 43 ]. Additionally, the role of sympathetic drive has been described in the impaired ventriculoarterial coupling of convalescent COVID-19 subjects [ 2 ], which may contribute to long COVID-19 symptoms, especially regarding functional status and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse wave velocity (PWV) including brachial-ankle pulse wave velocity (baPWV) and carotid-femoral pulse wave velocity (cfPWV) is indices of arterial stiffness. The result of a systematic review of the association between COVID-19 infection and vascular function determined by FMD and PWV implied that COVID-19 infection impairs vascular function, and exacerbates arterial stiffness and these effects persist after COVID-19 recovery [ 22 ]. The detailed mechanisms of how COVID-19 affects blood pressure through inflammation, sympathetic nervous system dysregulation, RAS activation, and even organ or vascular damage are unknown.…”
Section: Under the Covid-19 Pandemicmentioning
confidence: 99%